Availability of Therapies and Services for Parkinson's Disease in Africa: A Continent‐Wide Survey. Issue 10 (3rd June 2021) - Hamid, Eman; Ayele, Biniyam A.; Massi, Daniel Gams; Ben Sassi, Samia; Tibar, Houyam; Djonga, Emmanuel Epenge; El‐Sadig, Sarah Misbah; AMER EL KHEDOUD, Wahiba; Razafimahefa, Julien; Kouame‐Assouan, Ange Eric; Ben‐Adji, Djibrilla; Lengané, Yilédoma Thierry Modeste; et al.
Abstract: Background: The growing burden of Parkinson's disease (PD) in Africa necessitates the identification of available therapies and services to improve patient care. Objective: To investigate the availability, affordability, frequency of usage, and insurance coverage of PD therapies (pharmacological, surgical, physical, and speech therapies) and services including specialized clinics, specialists, and nurses across Africa. Methods: A comprehensive web‐based survey was constructed and distributed to neurologists/physicians with a special interest in PD across Africa. The survey instrument includes components that address availability, affordability, frequency of use, and insurance coverage of different therapies and services. Results: Responses were received from 28 (of 43 contacted) countries. Levodopa‐based oral preparations were always available in 13 countries (46.4%) with variable affordability and "partial or no" insurance coverage in 60% of countries. Bromocriptine was the most available (50%) and affordable ergot dopamine agonists (DA), whereas non‐ergot DA was always available in only six countries (21.4%). Trihexyphenidyl was the most available and affordable anticholinergic drug (46.4%). Tricyclic antidepressants and selective serotonin reuptake inhibitors were available in most countries (89.3% and 85.7% respectively), with variable affordability. Quetiapine and clozapine were less available. Specialized clinics and nurses were available in 25% and 7.1% of countries surveyed, respectively. Other services were largely unavailable in the countries surveyed. Conclusion: PD‐specific therapies and services are largely unavailable and unaffordable in most African countries. The data provide a platform for organizing strategies to initiate or scale up existing services and drive policies aimed at improving access to care and tailoring education programs in Africa. © 2021 International Parkinson and Movement Disorder Society